The XRCC4 rs1805377 polymorphism is not associated with the risk of cancer: An updated meta-analysis - Zhang, Xin-yuan (J Int Med Res, 2020)
OBJECTIVES: A growing number of studies have reported that genes involved in the repair of DNA double-strand breaks might be cancer-susceptibility genes. The x-ray cross-complementing group 4 gene (XRCC4) encodes a protein that functions in the repair of DNA double-strand breaks, and this meta-analysis aimed to investigate the relationship between the XRCC4 rs1805377 polymorphism and cancer occurrence. METHODS: We retrieved case–control studies that met the inclusion criteria from PubMed, Web of Science, Embase, and China National Knowledge Infrastructure databases. Associations between rs1805377 and cancer risk were evaluated by odds ratios (ORs) using a random effects model and 95% confidence intervals (CIs) as well as sensitivity and subgroup analyses. RESULTS: After inclusion criteria were met, the meta-analysis involved 24 studies that included 9,633 cancer patients and 10,544 healthy controls. No significant association was found between rs1805377 and the risk of cancer (pooled OR = 1.107; 95% CI = 0.955–1.284) in the dominant genetic model. Similarly, no significant association was observed in the subgroup analysis. CONCLUSIONS: Through this meta-analysis, we found no association between the rs1805377 polymorphism and cancer occurrence. This may provide useful information for relevant future studies into the etiology of cancer.